An Analysis of Speaking English Routine on Students’ Competences at Basic Level of Genta English Course Pare-Kediri - Fatqu Rofiqoh Dewi; Umrotul Islamiyah (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2022)
This study aims at improving the speaking competence of the basic level students of Genta English Course Pare Kediri. Speaking English routine were used in this study. This study is an action research study which comprised a class. It involved me as the researcher, the principle of Genta English Course, the English teacher, and 10 students of the basic level students of Genta English Course Pare Kediri. The steps of this study were observation, questionnaire, and documentation. The data of this study is qualitative. The qualitative data were obtained by observing the students’ competences in speaking English routine. The data were collected in the forms of field notes and questionnaire paper. And the last is by documentation, the data were collected in the performances in learning process. The research finding shows that the use of the speaking English routine is effective to improve students' speaking competence. English routine is accompanied with other actions such as using English classroom/dormitory, memorizing vocabularies, doing English language in any activities, giving feedback, giving rewards, and doing English program. The indicators of the success of the implementation are that: (1) the students are more active in the speaking English routine than they were; (2) the students are more enthusiastic in doing speaking English routine; and (3) the students' self-confidence and motivation to speak English improve. Furthermore, the findings are also supported by the means of the students' competences which have increased. Keywords : Speaking, English Routine, and Students’ Competences